Evaluation of serum biochemical parameters in juvenile bronze Turkeys (Meleagris gallopavo) - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos [UNESP]; Lapera, Ivan Moura [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; Junio, Leonildo Nardi [UNESP]; Testi, Alan Jonathan Pereira [UNESP]; Denadai, Janine [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP]; Fagliari, José Jurandir [UNESP] (My University, 2009)
The influence of age on serum biochemical parameters (AST, GGT, urea, uric acid, urea/uric acid ratio, total proteins, albumin, globulins and A/G ratio) was investigated in juvenile turkeys. Statistical comparisons were made for differences in values among different ages, from 76-148 day-old turkeys. Significant variations were observed in the analyses in relation to age of the birds for urea, AST and total proteins. This study also aimed to determine serum biochemical values for turkeys. © Asian Network for Scientific Information, 2009.
Keywords: Meleagris gallopavo; Serum biochemistry; Turkeys; Aves